Efek Penambahan Sekam Padi Pada Berbagai Media Tanam Terhadap Pertumbuhan dan Hasil Jamur Tiram Putih (Pleurotus ostreotus) - Rosnina, A G; Wirda, Zurrahmi; Aminullah, Agus (Faculty of Agriculture, Universitas Malikussaleh, 2017)
The purpose of this research is observe the effect of rice husk addition on various growing media on its growth and yield of white oyster mushroom (Pleurotus ostreatus). This research used Complete Random Design (CRD) Factorial consisting of 2 factors with 3 replications. The first factor is the various media planting (M). Media of sawdust sengon (M1); Rice straw; M2 and dried banana leaf (M3). The second factor is the supply of rice husks consisting of. Without the provision of rice husk (P0); Provision of 10% rice husk (P1); Provision of rice husk 20% (P2). The best planting medium was found in the treatment of sawdust wood media sengon (M1). Besides, the addition of rice husk concentration has significant effect on all observation parameters. The best result was found in 20% rice husk. The interaction between treatment of planting media and rice husk giving significant effect on first harvest, the body diameter of fruit of first harvest and body diameter of fruit of second harvest